Compliance to Advisory Committee on Immunization Practices recommendations for pneumococcal vaccination. Issue 15 (1st April 2022) - Morga, Antonia; Kimura, Tomomi; Feng, Qi; Rozario, Nigel; Schwartz, Jason
Abstract: We evaluated compliance to the ACIP pneumococcal vaccination recommendations issued in 2014 for adults aged ≥ 65 years and in 2012 for adults with high-risk (HR) conditions. The MarketScan® Commercial and Medicare Supplemental databases (January 2007-June 2019) were used to identify the cohorts of interest. Analyses for adults aged ≥ 65 years were adjusted to account for missing vaccination history. Two HR cohorts were identified. The HR1 cohort included patients with immunocompromising conditions, functional or anatomic asplenia, cerebrospinal fluid leak, or cochlear implant. The HR2 cohort included patients with chronic heart, lung, or liver disease; diabetes mellitus; alcoholism; cirrhosis; or cigarette smoking. Full compliance for those aged ≥ 65 years or in the HR1 cohort was defined as receipt of PCV13 and PPSV23, and partial compliance was defined as receipt of PCV13 or PPSV23. For those in the HR2 cohort, full compliance was defined as receipt of PPSV23. Annual compliance rates were estimated using the Kaplan–Meier method. Among those aged ≥ 65 years, partial compliance at 4 years post index was 53% and full compliance was 17% in adjusted analyses. In subjects ≥ 65 years receiving the first vaccination, 42% received the second vaccination by year 4. For the HR1 cohort, partial compliance was 19% and full compliance was 5% at 6 years post index date. For the HR2 cohort, full compliance was 20% at 6 years, with the highest rate in patients with diabetes (27%) and the lowest rate in patients with alcoholism (8%). Additional efforts are needed to maximize compliance to the ACIP pneumococcal vaccine recommendations among adults ≥ 65 years of age and adults with HR conditions including streamlined recommendations and single-dose vaccines. These efforts may subsequently reduce the incidence and burden of pneumococcal disease.